The Children's Forgiveness Card Set: Development of a Brief Pictorial Card-Sorting Measure of Children's Emotional Forgiveness - Kemp, Emma; Strelan, Peter; Roberts, Rachel Margaret; Burns, Nicholas R.; Mulvey, Kelly Lynn (Frontiers in Psychology, 2021)
Friendships have important influences on children’s well-being and future adjustment, and interpersonal forgiveness has been suggested as a crucial means for children to maintain friendships. However, existing measures of preadolescent children’s forgiveness are restricted by developmental limitations to reporting emotional responses via questionnaire and inconsistent interpretations of the term ‘forgive’. This paper describes development and testing of concurrent and discriminant validity of a pictorial measure of children’s emotional forgiveness, the Children’s Forgiveness Card Set (CFCS). In Study 1, 148 Australian children aged 8-13 years (M=10.54, SD=1.35) responded to a hypothetical transgression in which apology was manipulated and completed the CFCS and extant measures of forgiveness and socially desirable responding. Following an exploratory factor analysis to clarify the structure of the CFCS, the CFCS correlated moderately with other forgiveness measures and did not correlate with socially desirable responding. Apology predicted CFCS responding among older children. In Study 2 an exploratory factor analysis broadly replicated the structure of the CFCS among a sample of N=198 North American children aged 5-14 years (M=9.39 years, SD=1.67). We also fitted an exploratory bi-factor model to the Study 2 data which clarified which cards best measured general forgiveness, or positive or hostile aspects of responding to transgressions. Apology once again predicted the CFCS, this time regardless of age. The CFCS appears a potentially valid measure of children’s emotional forgiveness. Potential applications and differences between explicit and latent forgiveness in children are discussed.